PENGARUH PESAN, SIKAP DAN PERILAKU KHALAYAK TERKAIT KONTEN YOUTUBE EDUKASI KOSMETIK DR. RICHARD LEE TERHADAP TINGKAT KEPUASAN PENGGUNA YOUTUBE - Ria Elfrida Gultom, (2022)
The development of beauty cosmetic users is growing rapidly. Beauty cosmetic users use beauty cosmetics for their daily needs. The rapid development of beauty cosmetics in the market has made many influencers create content about beauty cosmetic education. This makes dr. Ricard Lee made various educational videos about beauty cosmetics in detail with laboratory tests and gave an explanation of the dangerous ingredients in the composition of beauty cosmetics. He is a beauty doctor and youtuber who has 2.29 million subscribers. The message conveyed by him was very clear and detailed so as to make youtube users who watched the educational video of beauty cosmetics feel satisfied with the explanation given by dr. Richard Lee. Furthermore, the attitudes and behavior of the audience when using beauty cosmetic products are quite diverse. Many are already using safe cosmetic products, but some are still using dangerous cosmetics that offer immediate benefits to their users. The purpose of this study was to determine whether or not there was an influence of messages, attitudes and behavior related to the cosmetic educational content of dr. Richard Lee on the level of youtube user satisfaction and how much influence it has. Respondents in this study were 100 respondents who were a sample of the population, namely youtube subscriber dr. Richard Lee. This research method is quantitative with the type of explanatory research, survey research methods, and uses and gratification theory